Understanding Individual Tax Compliance in Indonesia: Evidence from a Qualitative Survey Using Thematic Analysis of Taxpayer Perceptions - Primandita Fitriandi; Supriyadi; Nur Farida Liyana; Agus Puji Priyono (Yayasan Ilomata, 2026)
This study examines individual taxpayer compliance within the context of Indonesia’s heterogeneous tax system, where low compliance remains a persistent challenge in optimizing state revenue. Addressing the limited use of qualitative, perception-based approaches in prior tax compliance research, this study extends existing multi-factor frameworks by offering a qualitative and integrative perspective on how cognitive, administrative, and psychological factors interact in shaping taxpayer behavior. A qualitative survey design was employed using a single open-ended question asking respondents to explain the main factors influencing individual tax compliance. Data were collected through an online questionnaire distributed to individual taxpayers from diverse professional backgrounds using purposive sampling. A total of 304 responses were obtained, of which 284 valid responses were analyzed. The data were processed using thematic analysis supported by NVivo to identify key patterns and themes derived from respondents’ narratives. The findings indicate that tax awareness and tax knowledge emerge as the most prominent themes associated with compliance behavior, followed by administrative factors, perceived benefits, and trust in government, while social influence and sanctions appear less significant. These results suggest that taxpayer compliance is more closely associated with internal motivations and system-related experiences than with external pressures. The relatively open-ended nature of responses provides contextual insights into how taxpayers interpret their obligations and the tax system. This study highlights the importance of strengthening targeted tax education, simplifying digital tax services, enhancing transparent communication of tax benefits, and reinforcing trust in government as key strategies to improve taxpayer compliance in Indonesia.